2023
DOI: 10.3389/fnut.2023.1229427
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of geriatric nutrition risk index on elderly patients after spinal tuberculosis surgery

Abstract: BackgroundSpinal tuberculosis (STB) is a significant public health concern, especially in elderly patients, due to its chronic and debilitating nature. Nutritional status is a critical factor affecting the prognosis of STB patients. The geriatric nutritional risk index (GNRI) has been established as a reliable predictor of adverse outcomes in various diseases, but its correlation with surgical outcomes in elderly STB patients has not been studied.ObjectiveThe study aimed to assess the prognostic value of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Further, 249 articles were removed due to non-relevance. 23 studies underwent full-text analysis and 14 were selected [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. All fourteen studies were retrospective observational studies carried out in China, Japan, the USA, and Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Further, 249 articles were removed due to non-relevance. 23 studies underwent full-text analysis and 14 were selected [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. All fourteen studies were retrospective observational studies carried out in China, Japan, the USA, and Turkey.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, well-known indicators,such as ESR and CRP concentration, are commonly used to evaluate the degree of inflammation in patients with tuberculosis 35 and are associated with the prognosis of STB 36 , 37 . Nutritional status is also a vital factor affecting the progression and prognosis of spinal tuberculosis patients, and research has shown that the serum ALB concentration is an important laboratory marker for predicting SCI and prognosis in STB patients 38 . In this study, we ultimately selected ten clinical parameters, including age, NEU, LYM, MONO, CRP, ESR, HGB, PLT, ALB, and complicated hypertension, to establish the predictive model.…”
Section: Discussionmentioning
confidence: 99%